Bakhtin Completely Naked - Frédéric François (Bakhtiniana: Revista de Estudos do Discurso, 2014)
A Reading of Bakhtin in a Dialogue with Voloshinov, Medvedev and Vygotsky...Or else: Dialogism, the Misfortunes of a Concept when it Grows too Big, but Still Is Dialogism all the Same